1987
DOI: 10.1128/aem.53.9.2119-2123.1987
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic significance of glycerol accumulation in exponentially growing yeasts

Abstract: Natural-abundance "3C-nuclear magnetic resonance spectroscopy has shown glycerol to be the major osmotically significant low-molecular-weight solute in exponentially growing, salt-stressed cells of the yeasts Saccharomyces cerevisiae, Zygosaccharomyces rouxii, and Debaromyces hansenii. Measurement of the intracellular nonosmotic volume (i.e., the fraction of the cell that is osmotically unresponsive) by using the Boyle-van't Hoff relationship (for nonturgid cells, the osmotic volume is directly proportional to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(62 citation statements)
references
References 32 publications
(45 reference statements)
3
59
0
Order By: Relevance
“…The compatible solutes have no net charge nor do they adhere to or react with intracellular macromolecules (Sleator and Hill 2001). The three most common compatible solutes in most bacteria are glycine betaine, carnitine and proline, while fungi have been reported to accumulate polyhydric alcohols to a concentration commensurate with their extracellular a w (Pitt 1975;Edgley and Brown 1978;Reed et al 1987;Ko et al 1994;Jay et al 2005).…”
Section: Microbiology Of Packagingmentioning
confidence: 99%
“…The compatible solutes have no net charge nor do they adhere to or react with intracellular macromolecules (Sleator and Hill 2001). The three most common compatible solutes in most bacteria are glycine betaine, carnitine and proline, while fungi have been reported to accumulate polyhydric alcohols to a concentration commensurate with their extracellular a w (Pitt 1975;Edgley and Brown 1978;Reed et al 1987;Ko et al 1994;Jay et al 2005).…”
Section: Microbiology Of Packagingmentioning
confidence: 99%
“…During exponential growth in the presence of high extracellular sodium chloride concentrations, the halotolerant yeast Debaryomyces hansenii achieves osmotic balance mainly by producing and accumulating glycerol (Gustafson and Norkrans, 1976;Gustafson, 1979;Adler and Gustafson, 1980;Nobre and da Costa, 1985a,b;Andrt et al, 1988). According to Reed et al (1987) glycerol may counterbalance up to 95% of the external osmotic pressure produced by added sodium chloride. Leakage of glycerol from the cells is counterbalanced by an active glycerol transport mechanism (Adler et al, 1985) which maintains a steady-state glycerol accumulation ratio which increases with the extracellular sodium chloride concentration (Gustafson and Norkrans, 1976;Adler et al, 1985;Andrt et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…These polyols are the main solutes accumulated in other yeasts when subjected to osmotic stress (Spencer & Spencer, 1978). As is found in ascomycetous yeasts (Reed et al, 1987;Van Eck et al, 1993), glycerol was present in all basidiomycetous yeast strains when grown at reduced a w (0.96) and these yeasts accumulate glycerol as the main osmolyte. Little attention has been focused on the osmolytes accumulated by basidiomycetous fungi under osmotic stress, but Jennings (1984) found that the three basidiomycetous fungi investigated were able to produce most of the osmolytes observed in this study.…”
Section: Discussionmentioning
confidence: 66%